Evaluasi pelaksanaan sistem dan prosedur penerimaan kas pada Badan Pengelola Pajak dan Restribusi Daerah Kabupaten Minahasa Selatan - Kapoh, Marshela Pinly; Karamoy, Herman; Sabijono, Harijanto (Universitas Sam Ratulangi, 2019)
One of which can be used as a source of local revenue is cash receipts in government agencies such as offices, other government agencies. As an autonomous region, a new paradigm has emerged in the Indonesian constitutional system which has implications for the implementarion of local government. The purpose of this study was to evaluate the implementation of the system and procedure for cash receipts at the regional tax and levies management agency in the Minahasa Regency. Based on the results of research that the implementation of system and procedures for cash receipts in the Agency for the management of tax and levies in the southern Minahasa regency is in accordance with Permendagri 59 of 2007. System and procedures for local tax and levies include registration, verification, printing, signing of tax invoice, stipulation, issuance, depositing, recording, and filling of tax documents to taxplayes or tax levies. Based on research in the field that the system and procedures for regional financial management contained in Permendagri 59 of 2007, especially in the southern Minahasa regency tax and levies management agency, have been carried out well, it is clear that overall the procedures for receiving cash from authorized officials. In accordance with the result of the study, it can be concluded several things including: the system and procedures for cash receipts blank letter of deposit (BLD) is one ot the very important documents udes in recording cash receipts at the local tax and levies management body in South Minahasa Regency.